2014
DOI: 10.5586/asbp.1988.009
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical studies of the herb, Tragopogon orientalis L. (Asteraceae). 2. Components of a methanol extract

Abstract: Vitexin, orientin, isoorientin, luteolin and apigenin were isolated from the herb, <em>Tragopogon orientnlis</em> L. The occurrence of quercetin and the phenolic acids: chlorogenic, homoprotoca-techuic, protocatechuic, caffeic, gentysic, p-hydroxybenzoic, m-hydroxybenzoic o-hydroxyphenylacetic, p-hydroxyphenylacetic, p-cumaric, syringic, vanillic, ferulic and salicylic, and of the sugars: glucose, fructose and sucrose was demonstrated chromatographically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In addition, we determined 157.8 μg of o-coumaric acid for aerial parts in our study. As Abdalla and Zidorn stated in their review on the use of Tragopogon species, their phytochemical and pharmacological properties [25], similar to our study, Smolarz and Krzaczek's studies found high apigenin, luteolin, syringic acid and caffeic acid levels in methanolic extracts of Tragopogon orientalis L. [26]. In this study, when evaluated in terms of DPPH radical scavenging activity, more activity was found in the aerial parts than in the root (0.60±0.01 mg/ml) (Fıgure 1).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we determined 157.8 μg of o-coumaric acid for aerial parts in our study. As Abdalla and Zidorn stated in their review on the use of Tragopogon species, their phytochemical and pharmacological properties [25], similar to our study, Smolarz and Krzaczek's studies found high apigenin, luteolin, syringic acid and caffeic acid levels in methanolic extracts of Tragopogon orientalis L. [26]. In this study, when evaluated in terms of DPPH radical scavenging activity, more activity was found in the aerial parts than in the root (0.60±0.01 mg/ml) (Fıgure 1).…”
Section: Discussionsupporting
confidence: 90%
“…Also chlorogenic acid, 4,5dicaffeoylquinic acid, scopoletin 7-oglucoside, vitexin, and orientin have been found in T. porrifolius aerial part [8]. In Smolarz and Krzaczek study [16], detected flavonoids in T. orientalis L. were apigenin, vitexin, luteolin, orientin, isoorientin, and quercetin. In another study performed by DAD UV-Vis HPLC, the amounts of ferulic acid (197.79 g⋅g −1 ), caffeic acid (278.72 g⋅g −1 ), resveratrol (13.95 g⋅g −1 ), sinapic acid (110.85 g⋅g −1 ), rutin (89.99 g⋅g −1 ), and gallic acid (1347.85 g⋅g −1 ) were determined in T. pratensis flower and gallic acid was the dominant, followed by caffeic acid [7].…”
Section: Determination Of Phenolic Compoundsmentioning
confidence: 93%
“…The Tragopogon dubius distribution is shown in Figure 1. [15,16] The utilization of agronomic material in wastewater treatment has been reported by scientists; however, no study has addressed the application of Tragopogon dubius for this purpose. The nature, type modification, and economic optimum points of this plant are the novel aspects of the present research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the widespread distribution makes it more economical, easy to access, and a candidate for regional studies and diversity in research topics. The Tragopogon dubius distribution is shown in Figure 1 [15,16] …”
Section: Introductionmentioning
confidence: 99%